Gene expression profiling of reproductive meristem types in early rice inflorescences by laser microdissection. (April 2016) - Harrop, Thomas W. R.; Ud Din, Israr; Gregis, Veronica; Osnato, Michela; Jouannic, Stefan; Adam, Hélène; Kater, Martin M.
Summary: In rice, inflorescence architecture is established at early stages of reproductive development and contributes directly to grain yield potential. After induction of flowering, the complexity of branching, and therefore the number of seeds on the panicle, is determined by the activity of different meristem types and the timing of transitions between them. Although some of the genes involved in these transitions have been identified, an understanding of the network of transcriptional regulators controlling this process is lacking. To address this we used a precise laser microdissection and RNA‐sequencing approach in Oryza sativa ssp. japonica cv. Nipponbare to produce quantitative data that describe the landscape of gene expression in four different meristem types: the rachis meristem, the primary branch meristem, the elongating primary branch meristem (including axillary meristems), and the spikelet meristem. A switch in expression profile between apical and axillary meristem types followed by more gradual changes during transitions in axillary meristem identity was observed, and several genes potentially involved in branching were identified. This resource will be vital for a mechanistic understanding of the link between inflorescence development and grain yield. Significance Statement: Rice inflorescence meristems undergo a series of transitions during differentiation; control of these transitions impacts adult inflorescence morphology and hence grain yield. Although some genes involved in these transitions have been identified, a full understanding of the gene networks controlling this process is lacking. Here we use laser microdissection and RNA sequencing to describe the landscape of gene expression in four different meristem types. This resource will be useful for understanding how gene expression patterns are integrated with environmental and epigenetic factors, and for comparative studies of domestication.